Trans athletes' resistance : the struggle for justice in sport - Greey, Ali Durham; Lenskyj, Helen Jefferson (Emerald Publishing Limited, 2023)
With sport representing one of the last bastions of binary thinking, trans and nonbinary athletes face formidable hurdles in their struggles for inclusion, acceptance, and freedom. Trans Athletes' Resistance: The Struggle for Justice in Sport documents and analyses individual and collective resistance initiated by trans and nonbinary athletes and allies across a range of social-cultural and geopolitical contexts, from community sport to high-performance competition. In addition to sociological investigations of global, national, and local resistance, contributors present case studies and first-person accounts of struggles to challenge structural barriers and interpersonal hostility. Challenging policy-makers' binary definitions of males and females, the dominance of the achievement model, and toxic masculinity within sporting subcultures, the book explores how trans and nonbinary athletes not only resist transphobic policies and practices but also create new models of inclusive sport. The book has important implications for gender-inclusive policy development. Contributors present new methodologies and ways of theorizing the complex relationships among sex, gender, and sexuality in the equally complex terrain of sport and physical activity.
Includes index.
Keywords: Transgender athletes.; Gender identity in sports.; Social Science, LGBTQ+ Studies, Transgender Studies.; Sociology: sport & leisure.; elektronické knihy; electronic books